Defoliation Significantly Suppressed Plant Growth Under Low Light Conditions in Two Leguminosae Species - Wang, Ning; Ji, Tianyu; Liu, Xiao; Li, Qiang; Sairebieli, Kulihong; Wu, Pan; Song, Huijia; Wang, Hui; Du, Ning; Zheng, Peiming; Wang, Renqing (Frontiers in Plant Science, 2022)
Seedlings in regenerating layer are frequently attacked by herbivorous insects, while the combined effects of defoliation and shading are not fully understood. In the present study, two Leguminosae species (Robinia pseudoacacia and Amorpha fruticosa) were selected to study their responses to combined light and defoliation treatments. In a greenhouse experiment, light treatments (L+, 88% vs L-, 8% full sunlight) and defoliation treatments (CK, without defoliation vs DE, defoliation 50% of the upper crown) were applied at the same time. The seedlings’ physiological and growth traits were determined at 1, 10, 30, and 70 days after the combined treatment. Our results showed that the effects of defoliation on growth and carbon allocation under high light treatments in both species were mainly concentrated in the early stage (days 1-10). R. pseudoacacia can achieve growth recovery within 10 days after defoliation, while A. fruticosa needs 30 days. Seedlings increased SLA and total chlorophyll concentration to improve light capture efficiency under low light treatments in both species, at the expense of reduced leaf thickness and leaf lignin concentration. The negative effects of defoliation treatment on plant growth and non-structural carbohydrates (NSCs) concentration in low light treatment were significantly higher than that in high light treatment after recovery for 70 days in R. pseudoacacia, suggesting sufficient production of carbohydrate would be crucial for seedling growth after defoliation. Plant growth was more sensitive to defoliation and low light stress than photosynthesis, resulting in NSCs accumulating during the early period of treatment. These results illustrated that although seedlings could adjust their resource allocation strategy and carbon dynamics in response to combined defoliation and light treatments, individuals grown in low light conditions will be more suppressed by defoliation. Our results indicate that we should pay more attention to understory seedlings’ regeneration under the pressure of herbivorous insects.